Caminhada e estilo de vida: implicações no lazer e na qualidade de vida - Augusti, Marcelo Roberto Andrade [UNESP] (2014)
The research aimed to investigate the walk as a feature of a lifestyle, focused on quality of life and leisure. From a historical perspective be found walking in the social sphere and thus determine a trajectory of its uses and cultural appropriations in Brazil. Established the route of this practice and adjacent activities, it was possible to establish relationships between walking, livelihoods and lifestyles that emerge from these contexts. Subsequent to the preparation of this historical overview, we seek, in the electronic domain, check for groups of hikers who met the profile sought. Peregrinosrp found the group of Ribeirão Preto / SP, which revealed elements that we consider appropriate to the purpose of the investigation, ie, walking as leisure, expression of a lifestyle and reverberating quality of life, but as something understood beyond the context of the exercise. The field research was carried out for a group event, a hike between the towns of Analândia / SP and São Carlos / SP, rural route in approximately nineteen kilometers, where, at the end of the activity, was taken to collect data from a sample of fifteen subjects via questionnaire and later an interview via email with the creators and organizers of the proposal. The results of the analysis of information, based on the concepts and definitions of leisure, quality of life and lifestyle, showed that walking Peregrinosrp expresses the feature that, in principle, we can interpret them as an expression of lifestyle focused on quality of life. However, we suggest that further investigation is succeeding with this proposal and on a larger scale, for the considered sample allowed us only partial interpretations of the phenomenon addressed, preventing generalizing considerations